2013
DOI: 10.1128/aem.03294-12
|View full text |Cite|
|
Sign up to set email alerts
|

Quantitative Detection of Viable Bifidobacterium bifidum BF-1 Cells in Human Feces by Using Propidium Monoazide and Strain-Specific Primers

Abstract: We developed a PCR-based method to detect and quantify viable Bifidobacterium bifidum BF-1 cells in human feces. This method (PMA-qPCR) uses propidium monoazide (PMA) to distinguish viable from dead cells and quantitative PCR using a BF-1-specific primer set designed from the results of randomly amplified polymorphic DNA analysis. During long-term culture (10 days), the number of viable BF-1 cells detected by counting the number of CFU on modified MRS agar, by measuring the ATP contents converted to CFU, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…In the present study, improvement of some symptoms was observed at CL, that is, after only 4 weeks of consumption of fermented milk. Because B. bifidum YIT 10347 is known to remain alive in the intestines [ 24 ], we speculate that consumption of B. bifidum YIT 10347 fermented milk ameliorates the intestinal environment, resulting in increased stress tolerance and improved gastrointestinal and psychological symptoms. Ongoing maintenance of this amelioration is a probable reason for the improvement seen after 4 weeks of consumption of fermented milk in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, improvement of some symptoms was observed at CL, that is, after only 4 weeks of consumption of fermented milk. Because B. bifidum YIT 10347 is known to remain alive in the intestines [ 24 ], we speculate that consumption of B. bifidum YIT 10347 fermented milk ameliorates the intestinal environment, resulting in increased stress tolerance and improved gastrointestinal and psychological symptoms. Ongoing maintenance of this amelioration is a probable reason for the improvement seen after 4 weeks of consumption of fermented milk in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Both culturable and non-culturable microorganisms from any fermented food and beverage may be identified using culture-dependent and -independent methods to document a complete profile of microorganisms, and also to study both inter- and intra-species diversity within a particular genus or among genera (Ramos et al, 2010 ; Greppi et al, 2013a , b ; Yan et al, 2013 ). A combination of Propidium MonoAzide (PMA) treatment on samples before DNA extraction and molecular quantifying method can be used to accurately enumerate the viable microorganisms in fermented foods (Desfossés-Foucault et al, 2012 ; Fujimoto and Watanabe, 2013 ).…”
Section: Taxonomic Tools For Identification Of Microorganisms From Fementioning
confidence: 99%
“…Ethidium monoazide (EMA) and propidium monoazide (PMA) are the DNA-intercalating dyes developed for v-PCR and several articles describe their individual use to quantify viable strains of lactic acid bacteria and probiotics (Fujimoto and Watanabe, 2013;Gobert et al, 2018;Kramer et al, 2009;Meng et al, 2010). Despite this, there is evidence that both PMA and EMA present limitations in their application as viability dyes.…”
Section: Introductionmentioning
confidence: 99%